OCCUPATIONAL SAFETY AND HEALTH (K3) BUDGET FOR CONSTRUCTION IN ACCORDANCE WITH THE OMNIBUS LAW - Sitanggang, Ariza Putra; Manurung, Edison Hatoguan; Purwanto, Dwi (LPPM Institut Pendidikan Nusantara Global, 2024)
This paper is prepared as one of the requirements for completing studies in the field of Civil Engineering. The topic we discuss in this paper is the Occupational Safety and Health (K3) Budget for Construction in accordance with the Omnibus Law. Our objective is to gain a comprehensive understanding of the Construction K3 Budget that aligns with the Omnibus Law in Indonesia and to analyze its impact on the construction industry in the country. The background of this topic is crucial considering the importance of understanding and implementing Occupational Safety and Health (K3) in the construction industry in Indonesia. With the changing times and technological advancements, K3 has become a critical aspect of carrying out construction activities. Therefore, we find it essential to explore and deepen our understanding of the K3 Budget to provide a comprehensive understanding to the readers. In this paper, we will delve into the K3 Budget and the laws regulating it. We will elaborate on the concepts, theories, and principles related to Construction K3. Additionally, we will involve analysis and a review of relevant literature to support our understanding and arguments. We hope that this paper can be beneficial and make a meaningful contribution to both the professional and academic realms. We also aspire for this paper to serve as a useful reference for readers interested in further studying the Construction K3 Budget. In conclusion, we express our gratitude to all those who have assisted and supported us in preparing this paper. Without their help and support, this paper would not have come to fruition. We hope that this paper proves to be useful and provides valuable insights to the readers.